Dramat Praskiej Wiosny z perspektywy Śląska Opolskiego - Bereszyński, Zbigniew (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
The Prague Spring is a significant part of the history of Opolian Silesia – a region in Poland bordering Czechoslovakia. The course of the military invasion of Czechoslovakia and events in this country and within Polish-Czechoslovak borderland are reflected in documents and other material created by the authorities of the Opole voivodeship (province), which are presented in this paper.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne